Classification of Words of Wisdom in Indonesian on Twitter Using Naïve Bayes and Multinomial Naive Bayes: Klasifikasi Kalimat Mutiara Berbahasa Indonesia Pada Twitter Dengan Menggunakan Naïve Bayes dan Multinomial Naive Bayes - Andry Rachmadany; Yuliana Melita Pranoto; Gunawan Gunawan (Academia Open, 2020)
Quote is a sentence made with the hope that someone becomes a strong personality, an individual who always improves himself to advance and achieve success. Social media is a place for people to express their hearts to the world which is sometimes a heart expression in the form of quotes. The purpose of this study is to classify Indonesian quotes on Twitter using Naïve Bayes and Multinomial Naïve Bayes. This experiment uses text classification from Twitter data written by Twitter users whether the quotes are then classified again into 6 categories (Love, Life, Motivation, Education, Religion, Others). The language used is Indonesian. The methods used are Naive Bayes and Multinomial Naïve Bayes. Results of this experiment is a classified Indonesian quote collection web application. This classification makes it easy for users to search for quotes based on class or keyword. For example, when a user wants to search for 'motivational' quotes, this classification can be very useful.